Pre- and Postemergence Herbicides for Use Around Palms and Cycads - Robert H. Stamps; Jeffrey G. Norcini; Timothy K. Broschat; Charles W. Meister (EDIS)
ENH-1070, a 9-page fact sheet by Robert H. Stamps, Jeffrey G. Norcini, Timothy K. Broschat, and Charles W. Meister, lists herbicides for use in nurseries to reduce weed management costs in nurseries and maintenance costs in landscapes. Includes a table of tolerant palms and cycads for pre-emergent and post-emergent herbicides. Published by the UF Department of Environmental Horticulture, August 2007.